2020
DOI: 10.1186/s13075-020-02186-z
|View full text |Cite
|
Sign up to set email alerts
|

The regulation and pharmacological modulation of immune complex induced type III IFN production by plasmacytoid dendritic cells

Abstract: Objective: Patients with systemic lupus erythematosus (SLE) have an ongoing interferon (IFN) production due to an activation of plasmacytoid dendritic cells (pDCs), which can be triggered to type I IFN synthesis by RNA containing immune complexes (RNA-IC). Considering emerging data suggesting a role of type III IFN in the SLE disease process, we asked if RNA-IC can induce type III IFN production in pDC and how this production can be regulated. Methods: Peripheral blood mononuclear cells (PBMCs) or immune cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Measurement of protein levels of IFN-α in serum is a less sensitive assay than the IGS, herein detecting IFN-α in only 22% of the SLE cases. This could possibly be explained by the fact that patients were well controlled and used antimalarial agents to a high extent ( 30 ). Still, and in line with the report by Matsuoka et al, levels of galectin-9, as well as CXCL10, CCL2, and CCL19, were significantly higher among those with detectable serum IFN-α than among the others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of protein levels of IFN-α in serum is a less sensitive assay than the IGS, herein detecting IFN-α in only 22% of the SLE cases. This could possibly be explained by the fact that patients were well controlled and used antimalarial agents to a high extent ( 30 ). Still, and in line with the report by Matsuoka et al, levels of galectin-9, as well as CXCL10, CCL2, and CCL19, were significantly higher among those with detectable serum IFN-α than among the others.…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro experiments revealed different responses of IC induced versus TLR7/8-induced production of cytokines and galectin-9. This may indicate a complexity of IC induced responses in a mixed cell culture that, on one hand, activates TLR-7 and type I IFN regulated genes (30), but on the other hand stimulates chemokine production independent of TLR-7/8 activation. Another explanation could be that TLR7/8 activation results in different inflammatory profiles depending on the agonist, previously shown by Berggren et al (39).…”
Section: Aps (16)mentioning
confidence: 99%
“…These cells accumulate in the skin of mice with lupus and produce IFNλs in response to TLR7 agonists 35 . In humans, RNA-containing immune complexes can induce the production of type III interferons in a subset of pDCs that also produce type I interferons 77 . The production of IFNλs by pDCs in vitro was attenuated in the presence of hydroxychloroquine or an IL-1 receptor associated kinase 4 (IRAK4) inhibitor, indicating that RNA-containing immune complexes induce the production of IFNλs through the endosomal TLR–myeloid differentiation primary response protein (MyD88) system.…”
Section: Ifnλs In Autoimmune Rheumatic Diseasesmentioning
confidence: 99%
“…In addition to biologic agents that target BDCA2 or LILRA4, a variety of drugs can inhibit interferon production by other means. Antimalarial drugs such as hydroxychloroquine are commonly used to treat SLE and can inhibit type I and type III interferon production by pDCs in response to TLR7 or TLR9 stimulation 77 , 148 . Other TLR inhibitors are currently in various stages of development 149 .…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…Inside these droplets, cells receive their input while being excluded from any kind of interaction with other cells, thereby revealing their intrinsic behaviors upon single-cell activation. This change in approach revealed that upon single-cell activation only fractions of 1-3% produce IFN-Is, which is a phenomenon that has been observed in multiple different settings, for different types of immune cells, both in vitro and in vivo ( 17 21 ). Additionally, IFN-I priming revealed the crucial role of paracrine signaling in amplifying the TLR-induced IFN-I response by increasing the fraction of IFN-producing pDCs up to 40%, which comes to a halt upon the administration of neutralizing antibodies ( 16 ).…”
Section: Introductionmentioning
confidence: 99%